Peer review in the global digital age: perspectives of publishing industry stakeholders - Dikran Toroser; Muhammad Sarwar; Lisa DeTora; Laura Dormer; Maryam Sayab (European Science Editing, 2023)
Peer review is a crucial component of the scientific publication process, enabling validation of research, identification of errors, and removal of potential bias. However, there are some well-known limitations, including slow publication cycles and overstringent gatekeeping. Artificial intelligence and digital technology are revolutionizing peer review and publishing by addressing some of the limitations, and fostering closer collaboration among scholars worldwide.1-3 This paradigm shift aligns with the principles of open science, enhancing the reach and impact of scholarly work. Digital tools for peer review are already transforming many aspects of this process, by enhancing quality control, automation of routine tasks, and expediting laborious aspects of the peer review process, thereby enhancing speed and efficiency. Digital platforms are reducing publication times and potentially allowing for the promotion of diversity and inclusivity of the peer reviewer pool by vastly enhancing global connectivity. Selecting qualified and impartial global reviewers in the digital context is vital for the future of our rapidly evolving and increasingly diverse publication landscape. Editors play a key role in oversight while providing reviewers with clear guidelines and training. In conclusion, digital tools assisting peer review will inevitably play an increasingly useful role in enhancing the efficiency, and potentially the inclusivity and objectivity of the process.